Local Traditions as Guardians of Malay Identity among Pattani Muslims in Thailand - Puspita Sari, Indah (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2024)
Pattani as a region in southern Thailand is often plagued by conflict. This conflict can be traced back to the Anglo-Siamese treaty of 1909 which declared Pattani incorporated into Thailand. Since then, until now, the Pattani community, which is predominantly Muslim, has been at odds with the Thai government. The Muslim community living in Pattani has a different culture from the majority Thai-Buddhist community. The purpose of this paper is to write down the cultures of Pattani Muslims as a form of maintaining identity amidst the pressure of the Thai government. The method used is qualitative with data collection techniques by literature study, reviewing reading sources related to the theme, conducting interviews with 8 Muslims of Thai nationality, and watching YouTube channels that match the theme. The result is that the Pattani Muslim community maintains its traditions during a feud with the Thai government by continuing to use the Malay language, the Islamic education system, Islamic law still applies, marriage dowries, making pitue gates, doing rayo 6, serving special foods such as Ashura porridge. kerabu rice and ketupat, and wearing baju kurung as a symbol of identity. The research contribution is expected to provide insight into the Pattani Muslim community as a minority that maintains traditions as a sign of their identity under the pressure of the Thai government.